2011
DOI: 10.3329/ptcb.v21i2.10236
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Shoot Proliferation and Plant Regeneration of Phlogacanthus thyrsiflorus Nees. a Rare Medicinal Shrub of Bangladesh

Abstract: An efficient protocol was developed for shoot proliferation and plant regeneration of Phlogacanthus thyrsiflorus Nees. (Acanthaceae) - a rare medicinal shrub of Bangladesh, through in vitro culture using shoot tip and nodal explants. Best shoot induction was observed on MS with 1.0 mg/l BAP + 0.5 mg/l NAA, in which 84.2% of nodal explants responded to produce maximum number (12.4 ± 0.66) of shoots per culture. In vitro raised shoots rooted on half-strength MS with 0.5 mg/l IBA + 0.5 mg/l NAA. For acclimation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Al Khateeb et al [27] observed the maximum number of root induction in Lavandula coronopifolia at half-strength MS with 1.0 mg l 21 IBA. In contrast, Hassan et al [30] reported the highest number of root induction in Phlogacanthus thyrsiflorus on half-strength MS with 0.5 mg l 21 IBA and 0.5 mg l 21 IAA together. Cüce and Sökmen [31] observed the number of root induction in bog bilberry on MS with IBA, IAA, and NAA individually or together.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Al Khateeb et al [27] observed the maximum number of root induction in Lavandula coronopifolia at half-strength MS with 1.0 mg l 21 IBA. In contrast, Hassan et al [30] reported the highest number of root induction in Phlogacanthus thyrsiflorus on half-strength MS with 0.5 mg l 21 IBA and 0.5 mg l 21 IAA together. Cüce and Sökmen [31] observed the number of root induction in bog bilberry on MS with IBA, IAA, and NAA individually or together.…”
Section: Discussionmentioning
confidence: 86%
“…Kaushal et al [23], Deshpande and Bhalsing [7], and Haque et al [8] also reported a similar survival rate of hardening for different plantlets that support our present findings. Hassan et al [30] also reported the highest 85% survival rate after the acclimatization of Phlogacanthus thyrsiflorus plantlets in outdoor conditions.…”
Section: Discussionmentioning
confidence: 93%
“…(Acanthaceae), a rare medicinal shrub of Bangladesh, through in vitro culture using shoot tip and nodal explants. Best shoot induction was observed on MS with 1.0 mg/L BAP + 0.5 mg/L NAA, in which 84.2% of nodal explants responded to produce maximum number (12.4 ± 0.66) of shoots per culture (Hassan et al, 2011).…”
Section: Pharmacological Actionsmentioning
confidence: 98%
“…Hassan et al (2011) developed an efficient protocol for shoot proliferation and plant regeneration of P. thyrsiflorus Nees. (Acanthaceae), a rare medicinal shrub of Bangladesh, through in vitro culture using shoot tip and nodal explants.…”
Section: Pharmacological Actionsmentioning
confidence: 99%
“…It is a gregarious shrub with long orange-red tubular flowers and upright spikes at the end of branches, which are the major characteristics of the plant [3]. Traditionally, PT has been used against gout and rheumatism by the tribal people of Bangladesh [4].…”
Section: Introductionmentioning
confidence: 99%